Studi Komparasi Kinerja Keuangan Bank Syariah Indonesia dan Malaysia Dengan Pendekatan Sharia Conformity and Profitability Index (SCnPI) - M. Ujang Baihaqi; Evi Ekawati; Ahmad Habibi (ITB AAS INDONESIA, 2023)
Indonesia and Malaysia are two countries in Southeast Asia that are driving the development of the Islamic banking and finance system. Assessment of the soundness of banks needs to be carried out as a means of evaluating the conditions and problems faced by banks and determining follow-up actions to overcome bank weaknesses or problems. The method of measuring the performance of Islamic banks with the Sharia Conformity and Profitability (SCnPI) approach is more complex because it combines two assessment orientations that cannot be separated, namely the Islamic side of a bank and the financial side of a bank. This study aims to compare the performance of Islamic banks in Indonesia and Malaysia using the Sharia Conformity and Profitability Index (SCnPI) method. This research includes quantitative research with a comparative approach. This study uses secondary data originating from the financial statements of Indonesian Islamic Commercial Banks and Malaysian Islamic Commercial Banks for the 2015-2020 period. The sampling technique used was purposive sampling. The statistical software used is Version 25. The results show that there is no difference in financial performance with the Shariah Conformity and Profitability Index (SCnPI) approach from the Islamic Investment aspect of Sharia Commercial Banks in Indonesia and Sharia Commercial Banks in Malaysia for the 2015-2020 period. Then there are differences in financial performance with the Shariah Conformity and Profitability Index (SCnPI) approach from the aspect of Islamic Income, Profit Sharing Ratio, Return on Assets, Return on Equity and Net Profit Margin for Islamic Commercial Banks in Indonesia and Sharia Commercial Banks in Malaysia for the 2015-2020 period.